Perbaikan Waktu Set Up dengan Metode Single Minute Excange of Dies pada Mesin Die Casting - Ariyanto, Muchamad Septi; Ramayanti, Gina; Sahrupi, Sahrupi (Universitas Serang Raya, 2017)
The time needed to set up the production machine is 55 minutes. The high set-up time is caused by the non-differentiation of internal set-up and external set-up so that all set-up activities are carried out when the engine stops (internal set up). When viewed from the effectiveness of the company, the setup activities carried out at the time of the engine stop will significantly harm the company, which in turn will have an impact on the high bottleneck which results in delays in the production process in specific capacities. Research activities are carried out by direct measurement of die casting machines using a stopwatch. In this study, the authors conducted a study to apply the SMED method when setting up die casting machines at PT Mitsuba Indonesia. The SMED (Single Minute of Exchange Die) method as an approach is considered as one of the solutions used to reduce the setup time of the machine. From the results of the study, it was found that the set-up time was 35 minutes, or efficient by 64% on the set-up time before the repair.